Komposisi, Struktur, dan Stok Karbon Pohon Pada Sistem Agroforestri Berbasis jati di Desa Gemawang Wonogiri - Alifia Zahra Nanda Hasanah; Santhyami Santhyami (BIOEDUSCIENCE, 2023)
Background: The teak-based agroforestry system in Gemawang Wonogiri Village has the potential for various types of constituent tree vegetation that can act as carbon stock stores. This research was conducted considering the limited research on teak-based agroforestry systems, especially in the Wonogiri area. This study aims to provide information on tree vegetation's composition, structure, and diversity and determine the potential carbon stocks of tree vegetation standing in teak-based agroforestry systems. Methods: The research method used a 20 x 20 m2 plot of 1 ha, and the plots were placed using a purposive sampling approach. Results: Found nine species of tree vegetation from 8 families with 271 individuals ha-1. The species of teak tree (Tectona grandis) has the highest INP of 81.56 %. The Diversity Index is moderate, with a value of 1.79, and the Dominance Index is low at 0.21. The amount of carbon stored in tree stands is 45.71 MgC ha-1. Conclusions: This research can give information and points of reference about the structure and composition of stands in agroforestry systems and their potential to store carbon stocks. The research data is useful for the community as a source of information regarding the condition of the agroforestry area in Gemawang Village so that they can make optimal use of the area by developing suitable vegetation.